Edukasi Diet Diabetes Puasa untuk Mengendalikan Gula Darah Saat Menjalankan Puasa Ramadhan - Jaelani, Mohammad; Larasati, Meirina Dwi; Muninggar, Dian Luthfita Prasetya; Rosidi, Ali (Poltekkes Kemenkes Semarang, 2024)
Background: Fasting during Ramadan could have negative effects on individuals with Type 2 Diabetes Mellitus (T2DM), as it would lead to hypoglycemia or hyperglycemia. Non-compliance with the recommended diet during fasting is one of the factors that can trigger these conditions. Knowledge about the appropriate diet plays a crucial role in successfully adhering to the diet. Objective: The aim of this study is to assess the effect of providing T2DM education during Ramadan fasting on knowledge and fasting blood glucose levels. Method: This study is an experimental research conducted using a randomized controlled trial design with a pretest-posttest control group design. The participants of this study were T2DM patients from Tlogosari Kulon Community Health Center and Kedungmundu Community Health Center who were enrolled in the Prolanis program and did not have any complications related to kidney failure or stroke. A total of 46 participants were divided into a treatment group and a control group. The treatment group received nutritional education on managing their diet while fasting during Ramadan. This education was provided one week prior to the start of Ramadan fasting. Data collection included assessing knowledge, food intake, nutritional status, and fasting blood glucose levels before and after Ramadan fasting. The collected data will be analyzed using univariate analysis to describe the research data and to test the impact of nutrition education on knowledge and fasting blood glucose levels levels. The independent t-test with a significance level of α=0.05 will be used for this analysis.Result: There was a significant difference before and after being given nutrition education in intervention group on increasing knowledge levels in the intervention group (p=0.029) also lowering the blood glucose levels (p = 0.000). Providing education to the intervention group increased the knowledge score from 68.56 +12.81 to 79.26+9.47. There was an increase in knowledge leves by 10.70+3.34 in the intervention group. Nutritioneducation also reduced fasting blood glucose levels in intervention gropus from 177.78 + 79.61 to 141.35 + 43.78. There was a lowering in the blood glucose levels by -36.43 + 71.89 in the intervention group.Conclusion: There is a relationship between fasting ramadhan diabetes education with knowledge and blood glucose levels.